Heme oxygenase 1 controls early innate immune response of macrophages to Salmonella Typhimurium infection. (18th March 2016) - Mitterstiller, Anna‐Maria; Haschka, David; Dichtl, Stefanie; Nairz, Manfred; Demetz, Egon; Talasz, Heribert; Soares, Miguel P.; Einwallner, Elisa; Esterbauer, Harald; Fang, Ferric C.; Geley, Stephan; Weiss, Guenter
Summary: Macrophages are central for the immune control of intracellular microbes. Heme oxygenase 1 (HO‐1, hmox ) is the first and rate limiting enzyme in the breakdown of heme originating from degraded senescent erythrocytes and heme‐proteins, yielding equal amounts of iron, carbon monoxide and biliverdin. HO‐1 is strongly up‐regulated in macrophages in response to inflammatory signals, including bacterial endotoxin. In view of the essential role of iron for the growth and proliferation of intracellular bacteria along with known effects of the metal on innate immune function, we examined whether HO‐1 plays a role in the control of infection with the intracellular bacterium Salmonella Typhimurium. We studied the course of infection in stably‐transfected murine macrophages (RAW264.7) bearing a tetracycline‐inducible plasmid producing hmox shRNA and in primary HO‐1 knockout macrophages. While uptake of bacteria into macrophages was not affected, a significantly reduced survival of intracellular Salmonella was observed upon hmox knockdown or pharmacological hmox inhibition, which was independent of Nramp1 functionality. This could be traced to limitation of iron availability for intramacrophage bacteria along with enhanced stimulation of innate immune effector pathways, including the formation of reactive oxygen and nitrogen species and increased TNF‐α expression. Mechanistically, these latter effects result from intracellular iron limitation with subsequent activation of NF‐κB and further inos, tnfa and p47phox transcription along with reduced formation of the anti‐inflammatory and radical scavenging molecules, CO and biliverdin as a consequence of HO‐1 silencing. Taken together our data provide novel evidence that the infection‐driven induction of HO‐1 exerts detrimental effects in the early control of Salmonella infection, whereas hmox inhibition can favourably modulate anti‐bacterial immune effector pathways of macrophages and promote bacterial elimination.